Effect of the powder particle structure and substrate hardness during vacuum cold spraying of Al2O3. Issue 5 (1st April 2017) - Wang, Li-Shuang; Zhou, Heng-Fu; Zhang, Ke-Jie; Wang, Yu-Yue; Li, Cheng-Xin; Luo, Xiao-Tao; Yang, Guan-Jun; Li, Chang-Jiu
Abstract: In this paper, the effect of the powder particle structure and substrate hardness during vacuum cold spraying (VCS) of Al2 O3 is investigated. Our results help understand the underlying deposition mechanism during VCS in more detail and enable the tailoring and improving of the resulting coatings. Two structurally different alumina feedstocks were used for this study. We find that the loosely agglomerated powder bonds to the substrate primarily through coordinated deformation of the nano-sized powder particles. The sintered powder, on the other hand, bonds to the substrate through severe fracture and deformation of the particles. High-resolution transmission electron microscopy (HR-TEM) was employed to observe details in the interfacial microstructure of the coatings on the two substrates with differing hardness. The hard steel substrate facilitates particle fracture, which leads to cohesive particle/particle-bonding in the coating region close to the substrate. The softer aluminum substrate leads to strong interfacial coating/substrate-bonding because the particles are embedded into the substrate. In summary, the fracture and deformation of the feedstock as well as the substrate hardness affect both adhesion (coating/substrate bonding) and cohesion (particle/particle bonding) considerably.